2007
DOI: 10.1093/jn/137.4.992
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Markers of Systemic Inflammation among Iranian Women

Abstract: Few studies have examined the contribution of major dietary patterns to markers of systemic inflammation. This study was conducted to evaluate the association of major dietary patterns with markers of systemic inflammation among Iranian women. In a cross-sectional study of 486 healthy women aged 40-60 y, we assessed usual dietary intakes by means of an FFQ. Dietary patterns were identified by factor analysis. Anthropometric measurements were made and blood samples from fasting were taken for measuring inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
303
6
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 355 publications
(335 citation statements)
references
References 45 publications
19
303
6
7
Order By: Relevance
“…6 Dietary patterns including fruits, vegetables, whole grains, fish and different types of fatty acids, are inversely associated with different inflammatory markers. [37][38][39] In an intervention study, consuming a diet rich in SFA increased the concentrations of C-reactive protein, interleukin-6 and fibrinogen. 40 It has also been shown in a crosssectional design that a diet rich in omega-3 fatty acids is associated with lower amounts of pro-inflammatory markers and with higher amounts of anti-inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…6 Dietary patterns including fruits, vegetables, whole grains, fish and different types of fatty acids, are inversely associated with different inflammatory markers. [37][38][39] In an intervention study, consuming a diet rich in SFA increased the concentrations of C-reactive protein, interleukin-6 and fibrinogen. 40 It has also been shown in a crosssectional design that a diet rich in omega-3 fatty acids is associated with lower amounts of pro-inflammatory markers and with higher amounts of anti-inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…However, women with prior history of cardiovascular disease and diabetes were excluded from study sample to minimize the impact of these factors on analysis. In addition, women with these chronic diseases are more likely to have changed their diet [53,54], and this could bias the results toward null. Fifth, prevalence of smoking was low (only 5.7% smoking) and average minutes of exercise was high (over 150 minutes a week) in the study population.…”
Section: Discussionmentioning
confidence: 99%
“…Our validation study (27,28) with the use of biomarkers and also twelve 24 h dietary recalls as gold standard indicated that the FFQ provided a reasonably valid and reliable measure of intake for most food and nutrient intakes. Although we did not assess the correlation coefficients for DED per se, the correlations for fruits, vegetables and fats (the most influential factors on DED) were reasonable.…”
Section: Assessment Of Dietary Intakementioning
confidence: 90%